REFLEXIVITY: FROM GENERAL ABILITY TO THE ANALYSIS OF CONCRETE ACTIVITY: https://doi.org/10.5281/zenodo.20643130 - Obidova , Dilnoza (Scientific practical conference, 2026)
This article is aimed at analyzing the main dominant concepts of reflexivity, ranging from general ability to the analysis of concrete activity. These include descriptions of the concepts of reflexive thinking, reflection of activity, and reflexivity.